Factors Affecting The Success of High School Principals of West Lombok Regency in Implementing Their Leadership Functions Based on The Ministerial National Education Regulation No. 13 of 2007 - Waluyo, Untung; Asrin, Asrin; Muhaimi, Lalu (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
With the coming of educational reform in Indonesia, school principals are required to have adequate competencies to meet the national standards. The setting of this standard is intended to reduce the achievement gap among principals and ensure that all schools run the government policies. Minister of National Education (MONE) Regulation Number No. 13 of 2007 has mandated that every principalâs performance be evaluated on a regular basis. However, this evaluation has not revealed much the real condition in the field. For this reason, the current research attempts to evaluate success factors made by principals in performing 5 dimensions of leadership. The research was conducted in West Lombok Regency and employed a qualitative research design. Results of the study show that factors that determined principalsâ success in sustaining their leaderships, among other things, were their abilities to network, collaborate, develop partnerships, and meet teachersâ welfares and studentsâ achievements.